What Fanon said : a philosophical introduction to his life and thought - Gordon, Lewis R. (Lewis Ricardo), 1962- (Just ideas., 2015)
Antiblack racism avows reason is white while emotion, and thus supposedly unreason, is black. Challenging academic adherence to this notion, Lewis R. Gordon offers a portrait of Martinican-turned-Algerian revolutionary psychiatrist and philosopher Frantz Fanon as an exemplar of ""living thought"" against forms of reason marked by colonialism and racism. Working from his own translations of the original French texts, Gordon critically engages everything in Fanon from dialectics, ethics, existentialism, and humanism to philosophical anthropology, phenomenology, and political theory as well as ps